Performance analysis of Latvian zenith camera - Zariņš, Ansis; Rubans, Augusts; Silabriedis, Gunārs (Geodesy and Cartography, 2018)
Since finalizing of design in 2016, the digital zenith camera of the University of Latvia was involved in a number of test observations as well as field observations at about 70 different sites. The paper presents analysis of observation results, estimation of instrument’s performance and accuracy. Random and systematic error sources are outlined. Impact of anomalous refraction on vertical deflection determination is discussed. Results of adaptation of GAIA reference star catalog for astrometric data reduction are reported.